L2 grit: Passion and perseverance for second-language learning - Teimouri, Yasser; Plonsky, Luke; Tabandeh, Farhad (Language teaching research : LTR, 2022)
As a personality trait, ‘grit’ has been defined as a combination of perseverance and passion for long-term goals. Past research in social psychology has found grit as an important predictor of success across different populations in various academic and non-academic areas. Since successful mastery of a second language (L2) is highly dependent on learners’ sustained effort, the notion of grit and its relationship to language achievement gains immediate relevance in second language acquisition (SLA). The present study introduces the notion of grit and examines its relationship with motivational behaviors and language achievement in a sample of English as a foreign language learners (n = 191). Toward these ends, a language-specific grit scale was developed and validated to measure L2 learners’ grit. L2 grit was found to be positively related to students’ language learning motivation and achievement above and beyond domain-general grit. Taken together, and consistent with results of past research in social psychology, we propose that L2 grit be considered among other more established individual differences associated with L2 development.